Fire frequency affects fire behavior in open savannas of the Cerrado - Rodrigues, Cassy Anne [UNESP]; Zirondi, Heloiza Lourenço [UNESP]; Fidelis, Alessandra [UNESP] (Elsevier, 2021)
Fire is an environmental factor that helps in shaping plant communities by influencing their structure and function. Frequency is an important component of the fire regime. In tropical savannas, fire frequency is high, mostly owing to the high production and accumulation of fuel, which mainly comprising grasses, the dominant growth form in the Cerrado (Brazilian savanna) open physiognomies. We evaluated how the quantity, quality, and horizontal and vertical distribution of fuel influence fire behavior. We performed fire experiments with different fire frequencies (annual and biennial, from 2013 to 2017) in open savannas of the Cerrado (Central Brazil). Before each experimental fire, the quantity and distribution of the fuel as well as the moisture content and estimated the percentages of bare soil, dead biomass, and grass cover in the community were evaluated. During the experiments, we measured wind speed, air temperature, and fire behavior parameters, such as flame height, fire propagation rate, flame temperature, and residence time of the fire. Finally, we calculated fire intensity. Annually burned plots showed a lower fuel load and higher percentages of bare soil than biennially burned plots. Regarding the fire parameters, the intensity, flame height, maximum temperatures, and residence time were lower in the annually burned plots than in biennially burned plots. After four years of fire treatment, the annual fire frequency changed the vegetation structure, and the fire parameters responded to these changes. Thus, we conclude that the fuel load distribution influences fire behavior alongside the quantity of fuel in open savannas. The percentage of soil covered by each of the community structural components influences fire temperatures and residence time, which in turn affects fire severity. These findings allow for a more precise evaluation of the fire effects on plant communities facing fire behavior and help in developing better management plans.
Keywords: Fire intensity; Fire temperatures; Fuel load distribution; Fuel quantity; Plant community structure; Residence time of fire